Onwudinuba and the Igbo Conception of Wealth: Death, Prosperity, and Ancestral Fulfillment in Indigenous Cosmology - Okeke, Johnson Ifeanyi (Millah: Journal of Religious Studies, 2025)
This study examines the indigenous Igbo philosophy of Onwudinuba—the idea that death is a component of wealth—in order to reconceptualize wealth beyond narrow material definitions. It aims to demonstrate how, within Igbo cosmology, wealth (uba) is a holistic life project integrating material property, human reproduction, and a morally sanctioned “good death” that culminates in ancestral incorporation. The study adopts a qualitative, naturalistic research design grounded in interpretive and hermeneutic approaches, drawing on ethnographic fieldwork, participant observation, and in-depth interviews conducted across selected Igbo communities in southeastern Nigeria. Data were analyzed thematically to uncover indigenous categories of meaning embedded in language, ritual practice, and social norms. The findings reveal that Igbo wealth is evaluated retrospectively and communally, with death—specifically natural death accompanied by elaborate burial rites—serving as the final marker of a fulfilled life. Wealth-seeking is shown to be embedded in a moral economy that valorizes hard work, condemns laziness, institutionalizes entrepreneurship through the Igba boi apprenticeship system, and prioritizes procreation for lineage continuity and ritual remembrance. Funerary practices emerge as key arenas where material assets, social relations, and moral legitimacy are publicly transformed into symbolic capital. By integrating death into the analytic category of wealth, the study contributes a novel indigenous perspective to African philosophy, religious studies, and anthropological debates on prosperity and human flourishing. It underscores the importance of culturally grounded frameworks for understanding economic behavior, social policy, and end-of-life practices in African contexts.